Foreign Policy Preferences of Kazakhstan after 2022 - M. Y. Kucherov; I. V. Vokhmintsev; I. D. Kravchuk; V. Y. Andriukhin; M. A. Fedotov; A. A. Tokarev (Vestnik MGIMO-Universiteta)
The January 2022 protests in Kazakhstan drew global attention to the country's foreign policy orientations. This research investigates the focal states and international organizations prioritized by Kazakhstan during Kassym-Jomart Tokayev's presidency, spanning from March 20, 2019, when Tokayev assumed office, to December 31, 2022, marking the end of data collection. Employing content analysis and discourse analysis as primary methods, this study examines data from diverse sources, including the official website of Kazakhstan's President, his social media profiles, and relevant media outlets. The analysis encompasses mentions of countries, their leaders, and international organizations across three languages: Russian, Kazakh, and English.Key findings include Tokayev's frequent references to Russia (223 mentions) and China (95 mentions), while the United Nations (UN) and the Eurasian Economic Union (EAEU) receive the highest number of mentions among international organizations (178 and 102, respectively). Remarkably, Tokayev predominantly communicates in Russian when addressing foreign policy matters.In general, public discourse aligns closely with Kazakhstan's doctrinal discourse. However, notable discrepancies arise. Despite the Foreign Policy Concept's indication of Kazakhstan's intent to strengthen its strategic partnership with the United States, Tokayev's limited mentions of the United States (33 in total) suggest a distinct trend.